Effect of Structural Parameters on the Vibration of Slewing Bearing Under External Loading - Peng Zhou; Qian Wang; Wen Li; Zinan Wang; Jiacan Xu; Siqi Niu (Shock and Vibration)
As the main bearing component of the tunnel boring machine (TBM), the three-row roller slewing bearing is required to withstand a heavy load and overturning moment in the tunnelling process. Therefore, a dynamic model of a slewing bearing considering the external load and internal structural parameters is established. First, the influence of the complex load on the internal structural parameters (clearance, radial displacement, roller tilt and skew) of the slewing bearing is analysed. Then, by using the four-stage Runge–Kutta method, the dynamic model is solved, and the influence of different parameters on the dynamic performance and stability is obtained. Finally, the proposed model is verified via experimental research, and the accuracy error of the model is less than 7%. The state of the inner ring’s motion progressively changes from stable to unstable as the rotational speed increases. The dynamic characteristics of a slewing bearing can be improved by reducing the radial clearance and the number of rollers while it is subjected to excessive eccentric loading. The results of this study provide important guidance for the design of slewing bearing structures.